Stressors and coping styles of nursing students in the middle period of clinical practicum: a qualitative study - Fengzhen Li; Yawei Zeng; Yingjie Fu; Yuenv Wang; Tingting Lin; Qianying Deng; Jufang Li (BMC, 2024)
Abstract Background Nursing students encounter various stressors during their clinical practicum; however, the stressors are not the same during different periods. At present, studies on the stressors and coping styles of nursing students in the middle period of their clinical practicum are rare. Aims The current study aimed to explore the stressors and coping styles of nursing students in the middle period of their clinical practicum. Methods A qualitative study with a descriptive phenomenological method was conducted to collect data from 10 nursing students undergoing the middle period of their clinical practicum from December 2020 to February 2021. The data were collected by semistructured interviews using interview outlines prepared in advance. The data were analyzed by Colaizzi's analysis method. Results The stressors experienced by nursing students in the middle period of their clinical practicum mainly included personal reasons, teaching arrangements, interpersonal relationships, occupational particularity and career planning. Additionally, nursing students coped with the stressors that they face in the clinical practicum by eliminating stressors and regulating emotions. Conclusions Nursing students experienced various stressors and used a variety of coping styles in the middle period of their clinical practicum, which was different from what occurred in the early and late periods. Targeted interventions should be formulated and implemented to relieve nursing students' stress and guide them to adopt effective coping styles.